The power of economic textbooks: A discourse analysis - Lukas Bäuerle (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2019)
By conducting a discourse analysis (SKAD) in the field of academic economics textbooks, this paper aims at reconstructing frames and identity options offered to undergraduate students relating to the questions "Why study economics?"and "Who do I become by studying economics?". The analysis showed three major frames and respective identity offerings, all of which are contextualized theoretically, with prominent reference to the Foucauldian reflection of the science of Political Economy. Surprisingly, none of them encourages the student to think critically, as could have been expected in a pedagogical context. Taken together, economics textbooks appear as a "total structure of actions brought to bear upon possible action" (Foucault), therefore, as a genuine example of Foucauldian power structures.
Keywords: A11; A14; A20; A22; 330; Economic education; textbook economics; discourse analysis; SKAD; Foucault; subjectivation